Polish Jews in Africa in the interwar period = Żydzi polscy w Afryce w okresie międzywojennym - Knopek, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the emigration of Polish Jewish community to the individual regions in Africa in the years 1918-1939. It is stated in it that Africa was not really popular among Polish immigrants. Before 1939 only about 4200 people who had Polish citizenship lived on this large continent.
Keywords: Jews; Africa; Poland; emigration; Żydzi; Afryka; Polska; emigracja